Evaluating the Impact of a Video-Assisted Teaching Program on Knowledge and Attitudes About Teenage Pregnancy Prevention Among Fortunetellers Community Women in a Selected Region of Madurai District - R. Visali; Shanthi P.; Merlin Jeyapal; C. Jothi Sophia; Y. John Sam Arun Prabu; A. Priyasahaya Kaviya (International Journal of Evidence Based Nursing And Practices, 2024)
This research aims to evaluate the efficacy of a video-assisted teaching program in preventing teenage pregnancy, gauge participants' knowledge and attitudes regarding teenage pregnancy prevention, explore the relationship between their knowledge and attitudes, and examine how demographic variables correlate with pre-test knowledge and attitudes. The research hypotheses were formulated to determine their significance. A survey of the literature was done and organized based on studies related to teenage pregnancy. The theoretical basis of this study is rooted in the general system theory by Luding Von Bertalanffy, published in 1995. Reliability was established by Cronbach’s alpha method. The findings revealed that in experimental and control group in pre-test 29 (96.70%) and 27 (90%) of respondents had inadequate level of knowledge. In post-test, majority 20 (66.70%) of them had adequate and 18 (60%) of them had inadequate level of knowledge. There was more improvement on post-test in experimental than in the control group due to the effect of the intervention. In the pre-test, 29 participants (96.7%) in the experimental group and 28 (93.3%) in the control group displayed moderately favorable attitudes. Following the intervention, in the post-test, the majority of the experimental group, 28 (93.3%), maintained a moderately favorable attitude, while only 2 (6.7%) showed a favorable attitude. These results indicate that the video-assisted teaching program effectively enhances knowledge and fosters positive attitudes towards preventing teenage pregnancy.
Keywords: Assessment; attitude; effectiveness; fortunetellers community women; knowledge; teenage pregnancy; video-assisted teaching program